PERKEMBANGAN PEMIKIRAN DAN PENGATURAN PENYALAHGUNAAN WEWENANG DI INDONESIA (TINJAUAN SINGKAT DARI PERSPEKTIF HUKUM ADMINISTRASI NEGARA PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 30 TAHUN 2014) - Yulius, Yulius (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
The authority abuse is a concept that is always develop behind the realm of public law. This concept is an important measurement, for the wheels of the government. The actions and/or decisions of the agency and/or government officials are not unlimited authority. It is important for restriction or agency that oversees the actions and/or decisions of the government. The institution in question is the judiciary. Post the normalization of authority abuse in the Act No.30 of 2014 About Administration (particularly Article 21), there are different views in dealing with law enforcement. This is related to the absolute competence of the judiciary, namely the Administrative Court and the General Court (Criminal/Corruption). In that case, there needs to be clarity of meaning in the norms that regulate the abuse of authority. To avoid confusion in its implementation. Therefore, the need for understanding the meaning of abuse of authority by evaluating them in terms of the development of thinking and the settings from the perspective of administrative law.Keywords: Meaning, Authority, Law Enforcement